Aboriginal midwifery and traditional birthing systems revisited and revitalized: Interviews with First Nations elders in the Northwest region of British Columbia. - Ross-Leitenberger, Kimberly Ann (Author); Mills, Antonia (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 1999)
No abstract available. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1197319